Evaporative cooling with a wet fabric blanket for non-refrigerated horticultural produce transport: An experimental study - Nattawut Chaomuang; Onrawee Laguerre; Suriyan Supapvanich; Denis Flick; Steven Duret (My University, 2024)
Due to the high cost of mechanical refrigeration, Evaporative Cooling (EC) can be an alternative technology for small farmers in developing countries, such as Thailand. This study aimed to experimentally investigate the performance of EC using a wet fabric blanket. A real-scale cargo chamber, commonly used in Thailand, was constructed, and equipped with axial fans to simulate airflow during transportation. Two pallets of test products (hollow plastic balls) were loaded into the cargo and covered with the wet blanket. During the experiment, the inlet air velocities varied from 0.8 m s−1 to 3.6 m s−1 while the constant climate conditions were maintained (29–30 °C and 70–73 %RH). The air and product temperatures and air relative humidity were measured every minute for 3 h using thermocouples and hygrometers, respectively. The proposed EC method allowed the air temperature to decrease by approximately 3–4 °C. When the inlet air velocity decreased, a lower temperature reduction was observed. Simplified heat and mass transfer models were developed to interpret the load temperature evolution from the inlet to the outlet positions at different air velocities. The comparison between the measured and calculated data revealed a maximum mean relative error of 1.2 %. The quality preservation performance was also evaluated based on lettuce mass loss. Lower mass loss was observed for the product stored inside the cargo chamber (<6 %) compared to those outside (8–10 %). This study suggests the potential use of a wet blanket as an EC cooling medium for a short-distance transport to enhance the cold chain performance in Thailand.
Keywords: Thermocouple; Evaporative cooler; Pallet; Forced-air; Air velocity; Greenhouse Technology and Climate Control